Oral lesions, chronic diseases and the risk of head and neck cancer. Issue 12 (December 2015) - Li, Shuang; Lee, Yuan-chin Amy; Li, Qian; Chen, Chien-Jen; Hsu, Wan-Lun; Lou, Pen-Jen; Zhu, Cairong; Pan, Jian; Shen, Hongbing; Ma, Hongxia; Cai, Lin; He, Baochang; et al.
Summary: Objectives: The aim of our study is to explore the role of the history of oral lesions and chronic diseases on the risk of head and neck cancer in a Chinese population. Materials and methods: Our case-control study included 921 head and neck cancer cases and 806 controls. We obtained medical history information by administering questionnaires to both cases and controls. We used unconditional logistic regression to estimate odds ratios for oral lesions and chronic conditions. Results: Oral submucous fibrosis (OR = 24.24, 95% CI = 7.39–79.52), oral leukoplakia (OR = 4.05, 95% CI = 2.44–6.71) and repetitive dental ulcers (OR = 5.12, 95% CI = 3.17–8.28) increased the risk of HNC. Depression was associated with HNC risk when adjusted for several covariates (OR = 2.10, 95% CI = 1.06–4.15), but the association was not statistically significant after adjusting for smoking and alcohol drinking (OR = 1.53, 95% CI = 0.72–3.25). Also, the crude OR suggested an association between diabetes and HNC risk (OR = 1.51, 95% CI = 1.09–2.11), but it was not significant after adjusting for confounders. Conclusion: Our study reported on strong associations between HNC risk and oral leukoplakia, oral submucous fibrosis, which is consistent with prior research. We also observed repetitive dental ulcer to be associated with HNC risk. Future studies may focus on studying the association between depression and HNC, using medical records or psychological evaluation results to get more accurate information about depression, with careful assessment of tobacco and alcohol history.